OPTIMISATION OF AN IN VITRO PROPAGATION PROTOCOL FOR A VALUABLE LILY (Lilium spp.) - Thi Thu Huong, Bui; Huy Gioi, Dong; Van Thang, Bui (Journal of Forestry Science and Technology, 2017)
Lily species have been used as ornamental plants for centuries. However, micropropagation of Lily in vitro depends on particular species. Therefore, in this study, a protocol for micro propagating Lily was optimized. The results indicated that in vitro type 1 Lily scales (near the basal stem) cultured on MS medium supplemented with 60 g/l saccharose, 0 g/l glucose, 0.5 mg/l BA, 0.1 mg/l NAA, 100 ml/l coconut water, 5.5 g/l agar and 1 g/l activated charcoal in full dark conditions is the best with the highest regeneration rate of bulbscale (3.68 bulblet/slice). In vitro Lily bulblets became healthy and bigger, formed roots in MS medium supplemented with 0.2 mg/l NAA. In vitro Lily bulblets were found unsurvival and ungerminated without pre-cold treatment. The cold treatment time can vary between 4, 6, and 8 or 10 weeks, that did not affect the plant height and leaf numbers. The studies also found that the weight of bulblets significant affect plantlet height and leaf numbers.